A three-hinge-line method for calculating the deformation process of thin plates under quasi-static axial loading. Issue 2 (3rd March 2020) - Yao, Shuguang; Tan, Bowen; Xu, Ping; Che, Quanwei
Abstract: This paper presents a modified calculation method for the crushing deformation of sheet metals, which is called the three-hinge-line method (THLM). Through developing the folding mechanism of a thin-walled square tube, the effect of the buckling curvature on thin plates is approximately considered by improving the original single hinge to three hinges, and a method for calculating the distance between the hinges is given. A program is designed for the solution of this problem. In addition to solving for the average force and energy, the deformation process and force-displacement curves are also included. The accuracy of the THLM can be checked by the finite element method (FEM). The good agreement between the methods shows that the compressive forces are predicted satisfactorily from the results of the proposed uniaxial crushing.